Pengembangan Model Bisnis Berkelanjutan untuk Produk Halal - Priyatno, Prima Dwi; Sayuti, Muhammad Noor (Universitas Pembangunan Nasional Veteran Jakarta, 2025)
Abstract This study aims to explore the development of sustainable business models for halal products in Indonesia, focusing on environmentally friendly and ethical production, distribution, and marketing aspects. The research combines data from literature review, academic journals, government policies, and recent news sources to provide a comprehensive overview of the opportunities and challenges faced by the halal industry. The findings indicate that Indonesia has significant potential to become a global halal sustainable industry hub through efficient production practices, the implementation of digital technologies such as blockchain for supply chain transparency, and green marketing strategies that broaden the halal market beyond Muslim consumers to a global audience. However, internal obstacles such as limited human resources and halal certification issues, alongside regulatory and market competition challenges, still need to be addressed. Key recommendations include strengthening Environmental, Social, and Governance (ESG) principles, multi-stakeholder pentahelix collaboration, human resource development, and regulatory harmonization to enhance the sustainability and global competitiveness of Indonesia’s halal industry. Keywords: Sustainable business model; Halal products; Indonesian halal industry Abstrak Penelitian ini bertujuan untuk mengeksplorasi pengembangan model bisnis berkelanjutan pada produk halal di Indonesia dengan fokus pada aspek produksi, distribusi, dan pemasaran yang ramah lingkungan dan etis. Studi ini menggabungkan data dari literatur, jurnal akademik, kebijakan pemerintah, dan sumber berita terkini untuk memberikan gambaran menyeluruh mengenai potensi dan tantangan dalam industri halal. Hasil penelitian menunjukkan bahwa Indonesia memiliki peluang besar menjadi pusat industri halal berkelanjutan melalui penerapan praktik produksi efisien, penggunaan teknologi digital seperti blockchain untuk transparansi rantai pasok, serta strategi pemasaran hijau yang memperluas pasar halal bukan hanya untuk konsumen Muslim, tapi juga pasar global yang lebih luas. Namun, masih terdapat hambatan internal seperti keterbatasan sumber daya manusia dan sertifikasi halal, serta tantangan regulasi dan persaingan pasar yang perlu diatasi. Rekomendasi utama penelitian ini meliputi penguatan prinsip Environmental, Social, and Governance (ESG), kolaborasi multi-pihak pentahelix, pengembangan kapasitas SDM, dan harmonisasi regulasi sertifikasi untuk mendukung keberlanjutan dan daya saing global industri halal Indonesia. Kata kunci: Sustainable business model; Produk halal; Industri halal Indonesia